Congenital Limb Deformities in a Neonatal Crossbred Pig - Michael C. Rahe; Laurence Evrard; Neil B. Holmes (Case Reports in Veterinary Medicine)
Purpose. To describe the pathology and imaging findings in two neonatal piglets with congenital limb deformities. Methods. The litter from a second parity crossbred sow presented with four mummified fetuses, three stillborn piglets, and two live piglets with notable limb deformities that were unable to effectively ambulate. The piglets were euthanized and submitted for gross and histological evaluation. Results. Both pigs had bilateral secondary cleft palates, with hypoplasia of the nasal turbinates, and external rotation of the forelimbs. One pig displayed bilateral cryptorchidism, markedly thin and shortened hindlimbs, and syndactyly of both hind feet. Radiographs and gross dissection confirmed the presence of single ossified proximal to distal phalanges of both feet, bilaterally shortened tibias with fibular aplasia, and delayed ossification of tarsal as well as carpal bones. Conclusions. To the author’s knowledge, this is the first reported case of hindlimb meromelia with syndactyly in a pig.